2015
DOI: 10.2337/dc13-1210
|View full text |Cite|
|
Sign up to set email alerts
|

Is There a Link Between Liraglutide and Pancreatitis? A Post Hoc Review of Pooled and Patient-Level Data From Completed Liraglutide Type 2 Diabetes Clinical Trials

Abstract: OBJECTIVETo report the incidence of pancreatitis in type 2 diabetes trials of liraglutide and details of all pancreatitis cases. RESEARCH DESIGN AND METHODSData from Novo Nordisk-sponsored trials with liraglutide (phase 2 and 3; NN2211 identifiers) completed by 19 April 2013 were pooled. All pancreatitis cases were reviewed. RESULTSTotal exposure to liraglutide and active comparators was 5,021 and 1,354 patientyears, respectively (n = 6,345 and 1,846, respectively). Eight cases of acute pancreatitis (AP) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 34 publications
(36 reference statements)
5
34
0
Order By: Relevance
“…There has been considerable interest in a potential association between the use of GLP-1-receptor agonists and pancreatitis and pancreatic cancer, although there is no consistent preclinical, pharmacovigilance, or epidemiologic evidence to date. [23][24][25] Higher levels of lipase and amylase were observed in the liraglutide group, a finding that is similar to results in other studies. 24 Blinded medications were to be stopped only in relation to confirmed pancreatitis as evaluated by the investigator.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…There has been considerable interest in a potential association between the use of GLP-1-receptor agonists and pancreatitis and pancreatic cancer, although there is no consistent preclinical, pharmacovigilance, or epidemiologic evidence to date. [23][24][25] Higher levels of lipase and amylase were observed in the liraglutide group, a finding that is similar to results in other studies. 24 Blinded medications were to be stopped only in relation to confirmed pancreatitis as evaluated by the investigator.…”
supporting
confidence: 81%
“…[23][24][25] Higher levels of lipase and amylase were observed in the liraglutide group, a finding that is similar to results in other studies. 24 Blinded medications were to be stopped only in relation to confirmed pancreatitis as evaluated by the investigator. There were 1.5 episodes of pancreatitis per 1000 patient-years of observation in both regimens combined, and there were numerically fewer acute or chronic pancreatitis events with liraglutide than with placebo.…”
supporting
confidence: 81%
“…In the other study in this issue, Jensen et al (20) pooled data from 18 randomized controlled trials (RCTs) conducted by the manufacturer of the glucagonlike peptide 1 analog liraglutide. The authors report eight events of acute pancreatitis in the liraglutide group versus one event in the comparator group, generating incidence rates of 1.6 and 0.7 per 1,000 patient-years, respectively (relative risk 2.1 [95% CI 0.3-16.0]).…”
Section: Dwilliam T Cefalu Editor In Chief Diabetes Carementioning
confidence: 99%
“…Rates of acute pancreatitis reported in observational studies in patients with T2D in other countries include the following: Taiwan: 2.77 patients/1,000 patient-years [28]; Canada, United States, and the United Kingdom: 1.49 patients/1,000 patient-years [29]. The exposure-adjusted incidence rates of acute pancreatitis in patients treated with liraglutide or exenatide have been reported as 1.6 cases and 5.7 cases/1,000 patient-years, respectively [5,7]. In global phase 3 studies of incretin-based therapies, including dulaglutide, amylase and lipase have been assessed together, and increases in both have been observed with GLP-1 receptor agonists (dulaglutide, liraglutide, and exenatide) and DPP-4 inhibitors (sitagliptin) [15,17,23].…”
Section: Discussionmentioning
confidence: 99%
“…Pooled analyses of studies of GLP-1 receptor agonists exenatide, liraglutide, and lixisenatide suggested a numerically increased incidence of pancreatitis with these drugs, but there were few cases [7,8]. After comprehensive review of data from study drugs in the incretin class from many sponsors, the United States Food and Drug Administration (FDA) and the European Medicines Agency (EMA) have stated that available evidence does not support concern about pancreatic safety with incretin-based thera-…”
mentioning
confidence: 99%